A novel thermal interface membrane structure based on phase change material for thermal management of electronics. (May 2023) - Zhang, Liyu; Zhang, Xuelai; Hua, Weisan; Gao, Liqiang; Xie, Wenhao; Zhang, Wenzhuang
Abstract: As an important part of the heat dissipation system of electronic devices, thermal interface membranes (TIM) can largely eliminate the interface thermal resistance between electronic devices and heat sinks. However, the minimum thickness of TIM which is constrained by the maximum assembly pressure that the electronic chip can withstand and the marginal cost caused by the continuous improvement of thermal conductivity makes the development of conventional TIM bottlenecked. This paper proposes a novel laminar temperature control structure based on form-stable phase change material with thermal-induced flexibility (TF-FSPCM). When the TF-FSPCM is thin (<500 μm), the structure appears as a TIM. Different from conventional TIMs, the structure provides a unique lateral thermal conductivity channel to increase the maximum heat flux. And the TF-FSPCM simultaneously solves the problem of excessive assembly pressure and leakage of PCM. 6 wt% EG increases the thermal conductivity of PCM by 223 %. When the carbon fiber net (CFN) is functional layer material, the actual thermal resistance of CFN-TIM is not >0.79 cm 2 K/W and the minimum theoretical thermal resistance is <0.1 cm 2 K/W at the preparation pressure in 0.04 MPa. In particular, the assembly pressure on TF-FSPCM is reduced to a normal level due to its excellent self-repair. In addition, the membrane structure of CFN greatly improves the tensile strength and puncture resistance so that it has a broader application prospect. Finally, the actual temperature control experiments show that the equilibrium temperatures of CFN-TIM and CFN/CF-TIM are reduced by 12.8 °C and 15.6 °C, respectively. This indicates that the membrane structure has a small actual thermal resistance and a large elastic modulus. And it proves that the unique lateral conduction channel of the laminar composite structure has the actual heat dissipation ability. Highlights: This paper proposes a novel laminated temperature control structure based on TF-FSPCM. The TF-FSPCM simultaneously solves the problem of excessive assembly pressure and leakage of PCM. This structure solves the problem of interface thermal resistance and has a unique lateral conduction channel.